Character and Values Education in the Türkiye Century Maarif Model: A Qualitative Document Analysis - Gürhan, Ethem (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2025)
This study critically analyzes how moral and civic values are represented and operationalized within the Türkiye Century Maarif Model (TYMM) for primary education through a qualitative document analysis approach. Using Braun and Clarke’s six-phase thematic framework, five official curriculum and policy documents published by the Ministry of National Education between 2023 and 2024 totaling approximately 450 pages were examined. The analysis identified four structural themes: Virtue (Erdem), Value (Değer), Action (Eylem), and Pedagogical Reflection, each illustrating how the TYMM transforms moral education from implicit moral instruction into an explicit, measurable, and pedagogically integrated framework. The findings reveal that the TYMM links personal morality with civic responsibility, embedding values such as honesty, justice, empathy, and cooperation within competency-based learning outcomes. While the model successfully harmonizes local moral heritage with global citizenship principles, it also reveals ideological tensions between universal ethics and national identity. Theoretically, this study contributes to moral and character education literature by offering a curriculum-level perspective on how values are linguistically structured and pedagogically operationalized. Practically, it provides a conceptual reference for educators and policymakers seeking to align moral formation with democratic and global educational goals.